HEAVY METALS DETECTION IN ATMOSPHERIC FALLOUT AND AMBIANT AIR - YOUNES KHDAYCHI; LAILA IDRISSI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
bstract: The air quality-monitoring network in Morocco does not cover all regions and occasionally gives data on atmospheric metallic particulate pollution. This work makes it possible to find a simple, inexpensive and available method for monitoring this type of pollutants. In this paper, we report an effective, simple, sensitive and low-cost electrochemical method for heavy metals monitoring in rainwater and airborne particulate matters. The glassy carbon electrode modified ex-situ with a thin mercury film (GCE/TMF) was used as a sensor to detect Cd2+ and Pb2+ by square-wave anodic stripping voltammetry (SWASV). The developed sensor showed a linear response in the concentration range of 0.1-2.0 µmol·L-1 in HCl 0.1 mol·L-1 for both Cd2+ and Pb2+ heavy metal ions. The calculated limits of detection were 12 and 16 nmol·L-1 for Cd2+ and Pb2+ respectively. Moreover, the proposed electrochemical sensor was successfully applied to monitor Cd2+ and Pb2+ in total atmospheric fallout (TAF) and particulate matter (PM10) samples collected in Mohammedia city. The obtained results showed some exceedances of the limit standards preconized for cadmium and lead elements.